Data Mining Techniques based on a Cloud Computing - Qwaider, Walid Qassim (Institut Teknologi Bisnis AAS Indonesia, 2024)
Data mining is an essential process as it is used to find and discover new, correct, useful and understandable forms of data. Cloud computing has become a multi-use technology for data processing, storage, and distribution, offering a wide range of applications and infrastructure such as the Internet service that customers can access from anywhere. The massive volume of data can have stored in low-cost cloud data centers. Both data mining and cloud computing technologies help business organizations maximize profits and reduce costs in different ways. The focus of this paper on data mining is the technique of knowing the previously unknown relationship and new patterns in extensive data that can even predict future decisions by using some useful algorithms and techniques such as classification, prediction, clustering, summarization, base assemblies, regression analysis, time series analysis.